MEMBANGUN KETAHANAN FINANSIAL DENGAN MENANGKAL BIAS KEUANGAN: EDUKASI UNTUK MASYARAKAT DI WILAYAH SUB-URBAN - Farizya, Abidara Wahyu; Rusdiana, Aura Ratu; Oktasyadita, Nasywa; Mulyantini, Sri; Fadila, Ardhiani (Universitas Muhammadiyah Tangerang, 2024)
Sub-urban communities often have characteristics that can lead to financial bias. Most sub-urban communities tend to have lower income levels, limited access to formal financial institutions, relatively low levels of financial education and literacy, and lack of exposure to financial information and education. The objective of this socialization program is to provide useful financial bias knowledge for communities in Sukabumi, Cibubur, and Pejaten areas to manage their finances more effectively. The methods used were observation, in-depth interviews, socialization and mentoring, and evaluation by providing questionnaires through google form. The results showed that before the socialization, 96.7% of respondents from Sukabumi, Cibubur, and Pejaten did not know framing bias, availability heuristic bias, self attribution bias, and representativeness bias and 93.3% did not know herding bias. After socialization, 100% of respondents were able to understand well framing bias, herding bias, self attribution bias, and representativeness bias and 96.7% were able to understand well availability heuristic bias.